PENGARUH PENGENDALIAN INTERNAL, TEKANAN EKSTERNALDAN KOMITMEN MANAJEMEN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN - Henny Setiawan (2017)
This research was conducted aiming to examine the magnitude of any causal relationships among variables The influence of internal control, external pressure and management commitment Towards The Implementation Of The Transparency Of Financial Reporting. Population in this research is Depok City Regional Device Organization. Sampling in this research is the Head and Staff of Finance Subdivision that work on Organization of Depok City Region. Samples used in this study are employees of finance and accounting in the amount of 80 respondents were selected using census method. The data were collected from a primary source in a form of quantitative data by using questionnaire, designed based on Liker scales. Analytical techniques used in this study using Partial Least Square (PLS). The results showed that there was an effect from each of the independent variables on the dependent variable, that the Internal Control and Management Commitment significant effect on the implementation of the transparency of financial reporting. While External Pressure not significant effect on the implementation of the transparency of financial reporting.